Assessment of a Model of Integrated Supervision on Communicable Disease Control of the Office of Communicable Disease Control Region 2, Saraburi - Ungkasrithongkul, Sujitra; Uengpanich, Varapom (Journal of Health Science of Thailand, 1994)
Office of Communicable Disease Control Region 2, Saraburi, has proposed a model of Integrated supervision on communicable disease control and Implemented in Singhaburi province for the first round of fiscal year 1993. The objective is to develop an appropriated supervision model. An assessment has been performed during implementation. The results showed that this model achieved the objective, accepted and appreciated by the Provincial Health staffs and applicable to operate in other provinces.